ANALISIS FUNGSI PENGAWASAN COMPLIANCE RISK MANAGEMENT MELALUI APPROWEB TERHADAP PENERIMAAN PAJAK BADAN KPP PRATAMA JAKARTA CAKUNG - Dina Fikri Hayati; Kadunci Kadunci; Titik Purwinarti (EPIGRAM (e-journal), 2022)
This article aims to describe the mechanism for implementing the Compliance Risk Management model of the supervisory function and its success rate on corporate tax revenue at KPP Pratama Jakarta Cakung. Efforts are being made to improve the supervision of tax revenues from each KPP area to the DJP environment, one of which is the improvement of a tool called Compliance Risk Management with the Circular Letter of the Director General of Taxes Number SE-39/PJ/2021. In increasing tax revenue, the supervisory function is important to find out more about taxpayers that need to be researched. Therefore, an overview of the Compliance Risk Map is needed that displays the entire Corporate Taxpayer by categorizing it into several levels of risk. This is expected to provide justice and equal distribution of the supervisory function carried out by tax officers to all taxpayers. Data collection techniques used 3 (three methods, namely semi-structured in-depth interviews, non-participatory observation, and documentation. Data interpretation was carried out in stages starting from collecting data, reducing data, to final conclusions. The results showed that the application of CRM in KPP Pratama Jakarta Cakung had an impact convenience, especially in carrying out the maximum supervisory function for tax officers. But on the other hand, tax revenue from 2020 to 2021 is still far from reaching the expected revenue target. This shows the need for a re-examination of the problems that continue to be faced by KPP Pratama Jakarta Cakung, and improve other CRM functions to be able to run in balance and produce better results.